The rule of nine : a Paul Madriani novel - Martini, Steve, 1946- (New York : Harper, 2011)
After a career terrorist threatens to destroy the Supreme Court in a single horrible act, defense attorney Paul Madriani must put his life on the line in order to stop the sinister deed before it comes to fruition.
Originally published: New York : William Morrow, c2010.
Keywords: United States. -- Supreme Court -- Fiction; Madriani, Paul (Fictitious character) -- Fiction; Radicals -- Fiction; Terrorism -- Fiction; Washington (D.C.) -- Fiction; Mystery fiction; Legal stories; Suspense fiction